Early Detection of Legionella pneumophila and Aspergillus by mNGS in a Critically Ill Patient With Legionella Pneumonia After Extracorporeal Membrane Oxygenation Treatment: Case Report and Literature Review - Yue, Ruiming; Wu, Xiaoxiao; Li, Tianlong; Chang, Li; Huang, Xiaobo; Pan, Lingai (Frontiers in Medicine, 2021)
Legionella pneumophila can cause human pneumonia even severe ARDS. Due to the harsh growth requirements, limited detection methods and non-specific clinical manifestations, the current diagnosis of Legionella pneumonia is still challenging. With the application of mNGS technology, the detection rate of Legionella increased. This patient in our study rapidly progressed to severe ARDS in the early stage and received ECMO treatment, but the traditional test of BALF and the serum antibody was negative, but the mNGS of the BALF and blood were Legionella pneumophila, and the patient recovered well according to the mNGS results in the initial stage. Searching pubmed found only a few reports of secondary Aspergillus infections after Legionella. In this case, the application of mNGS technology found that the patient had secondary Aspergillus infection at an extremely early stage with negative traditional culture. The early secondary infection of Legionella pneumonia subverts the traditional concept of high-risk factors for Aspergillus infection. Combined with previous reports on Aspergillus secondary to severe influenza, in fact, severe pneumonia caused by any kind of pathogenic bacteria may follow by Aspergillus infection, and sometimes in the extremely early stage. Therefore, this case reminds us that early screening for secondary infections of severe pneumonia should be strengthened, and if necessary, technologies such as mNGS can be used to detect pathogens early and achieve precise treatment as soon as possible, thereby simplifying the use of antibiotics and improving the prognosis.